DAMPAK PASTORAL SEKOLAH TERHADAP PEMBENTUKAN KARAKTER PESERTA DIDIK AGAMA KATOLIK SMP KATOLIK STA. MARIA ASSUMPTA KOTA BARU KUPANG - Ta’ek, Emilia Dolorosa; Je’eMaly, Emanuel Inocentius; Masan, Valentinus Kopong (Sekolah Tinggi Pastoral St. Petrus Keuskupan Atambua, 2024)
The aim of this research is to determine the influence of school pastoralism on the character formation of Catholic religious students at St. Catholic Middle School. Maria Assumpta New City Kupang. This study uses a qualitative method. The sample in this study was 30 people consisting of 1 school teacher, 24 teachers and 5 people. The data collection technique used in the research was carried out using interviews and documentation studies, while the data analysis technique in this qualitative research was by using the power collection, data reduction, data display and data ferifying techniques. The results of the research show that school pastoral care has a huge impact in shaping the character of Catholic students, this cannot be separated from the support and assistance of parents. This is shown through the results of research using interview methods with school principals, teachers and parents.